2015
DOI: 10.1111/mpp.12282
|View full text |Cite
|
Sign up to set email alerts
|

Citrus psorosis virus 24K protein interacts with citrus miRNA precursors, affects their processing and subsequent miRNA accumulation and target expression

Abstract: Sweet orange (Citrus sinensis), one of the most important fruit crops worldwide, may suffer from disease symptoms induced by virus infections, thus resulting in dramatic economic losses. Here, we show that the infection of sweet orange plants with two isolates of Citrus psorosis virus (CPsV) expressing different symptomatology alters the accumulation of a set of endogenous microRNAs (miRNAs). Within these miRNAs, miR156, miR167 and miR171 were the most down-regulated, with almost a three-fold reduction in infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
53
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 78 publications
(123 reference statements)
1
53
0
Order By: Relevance
“…Post-transcriptional alterations may include miRNA processing, accumulation and activity. Recent studies revealed that some viral proteins (VP) interfere with pre-miRNA nuclear export and processing by DICER, as is the case of adenovirus [ 15 ] and the Ophiovirus Citrus psorosis virus (CPsV) [ 16 ]. CPsV 24K protein interacts with pre-miR156 a and pre-miR171 a in Nicotiana benthamiana plants, causing a higher accumulation of unprocessed precursor species and a concomitant downregulation of mature miRNA species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-transcriptional alterations may include miRNA processing, accumulation and activity. Recent studies revealed that some viral proteins (VP) interfere with pre-miRNA nuclear export and processing by DICER, as is the case of adenovirus [ 15 ] and the Ophiovirus Citrus psorosis virus (CPsV) [ 16 ]. CPsV 24K protein interacts with pre-miR156 a and pre-miR171 a in Nicotiana benthamiana plants, causing a higher accumulation of unprocessed precursor species and a concomitant downregulation of mature miRNA species.…”
Section: Introductionmentioning
confidence: 99%
“…CPsV 24K protein interacts with pre-miR156 a and pre-miR171 a in Nicotiana benthamiana plants, causing a higher accumulation of unprocessed precursor species and a concomitant downregulation of mature miRNA species. Consequently, target transcript accumulation is upregulated, possibly leading to differential symptom expression [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many miRNAs have been reported to mediate plant responses to biotic stresses, including viruses, bacteria and fungi (Niu et al ., ). For instance, the expression patterns of selected miRNAs from the model plants Arabidopsis thaliana (Hu et al ., ), Nicotiana benthamiana (Pacheco et al ., ), Solanum lycopersicum (Feng et al ., ; Naqvi et al ., ), Oryza sativa (Sun et al ., ; Xu et al ., ) and Cucumis sativus (Liu et al ., ), and non‐model plants including Citrus sinensis (Reyes et al ., ), Carica papaya (Liu et al ., ), Brassica campestris (Wang et al ., ) and Hibiscus cannabinus (Gao et al ., ), are modified by virus infections. Alterations of miRNA levels by virus infection also influences symptom development and disease proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…Alterations of miRNA levels by virus infection also influences symptom development and disease proliferation. RNA viruses from different genera or families, such as Cucumber mosaic virus (CMV; Cucumovirus ) (Feng et al ., ), Turnip mosaic virus (TuMV; Potyvirus ) (Wang et al ., ), Cucumber green mottle mosaic virus (CGMMV; Tobamovirus ) (Liu et al ., ), Papaya meleira virus (PMeV; unclassified dsRNA virus) (Abreu et al ., ), Citrus psorosis virus (CPsV; Ophiovirus ) (Reyes et al ., ), Oilseed rape mosaic tobamovirus (ORMV; Tobamovirus ) (Hu et al ., ), Rice black‐streaked dwarf virus (RBSDV; Fijivirus ) (Sun et al ., ; Xu et al ., ), Hibiscus chlorotic ringspot virus (HCRSV; Carmovirus ) (Gao et al ., ), Potato virus X (PVX; Potexvirus ) (Pacheco et al ., ) and the DNA virus Tomato leaf curl virus (ToLCV; Begomovirus ) (Naqvi et al ., ), have all been reported to regulate host miRNA expression. These results indicate that the regulation of plant–virus interactions by miRNAs may be a common feature, and highlight the importance of further mining and determination of the functions of miRNAs during viral infections in different plant species.…”
Section: Introductionmentioning
confidence: 99%
“…Citrus psorosis virus (CPsV), the type member of the Aspiviridae family (formerly Ophioviridae), genus Ophiovirus (40,41), is a three-partite, nonenveloped, negativesense, single-stranded RNA (ssRNA) virus. RNA 1 encodes a 280-kDa replicase (42) as well as a 24-kDa protein that affects microRNA (miRNA) maturation (43) and has RNA silencing-suppressing activity (44). RNA 2 encodes a protein of 54 kDa (named here MP CPsV ), which displays several features of a MP (45,46) and has RNA silencingsuppressing activity as well (44).…”
mentioning
confidence: 99%